Meta-Analysis: Factors Related to Pap Smear Service Utilization Using Health Belief Model - Ayun Safitri; Argyo Demartoto; Hanung Prasetya (Journal of Health Promotion and Behavior, 2024)
Background: Cervical cancer or cervical cancer is the most frequently diagnosed cancer and the fourth leading cause of death from cancer in women. Regular cervical cancer screening with the Papanicolaou (Pap) smear test remains an effective public health intervention in preventing and reducing the incidence of cervical cancer morbidity and mortality. The health belief model (HBM) is a psychological health behavior change model which shows that belief, perception, and attitude about a disease determine their willingness to use preventive interventions such as disease screening. This study aims to analyze the effect of the health belief model on the utilization of Pap smear screening services. Subjects and Method: This was a systematic review and meta-analytic study. This study uses the PICO model. The meta-analytic study was carried out by searching for articles from databases in electronic form using PubMed, Google Scholar and Proquest. Article search was carried out for 1 month. The keywords used were “Cervical Cancer Screening” OR “Pap Smear” AND “Health Belief Model” OR “Health Belief” AND Cervical Cancer”. The inclusion criteria for this study were complete articles using cross-sectional, 2013-2023. Analysis of the articles in this study used RevMan5.3 software. Results: A total of 15 cross-sectional studies from several countries, namely Indonesia, Ethiopia, Ghana, Iran, Italy, Lebanon, South Korea and the United States. The results of the meta-analysis showed that women of childbearing age with a high perceived vulnerability had a 1.19 times higher likelihood of utilizing Pap Smear screening services than those with a low perceived vulnerability (aOR= 1.19; 95% CI= 1.08 to 1.32; p< 0.001). High perceived benefit (aOR= 1.12; 95% CI= 1.07 to 1.16; p< 0.001) and high self-efficacy (aOR= 1.17; 95% CI= 1.01 to 1.36; p= 0.040) increased utilization of Pap smear screening services. Conclusion: Perceived vulnerability, perceived usefulness and self-efficacy significantly influence the utilization of Pap Smear screening services